2006
DOI: 10.2344/0003-3006(2006)53[83:apsosr]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of 2 Sedation Regimens in Children: Chloral Hydrate, Meperidine, and Hydroxyzine Versus Midazolam, Meperidine, and Hydroxyzine

Abstract: The aim of this study was to compare both the behavioral and physiological effects of 2 drug regimens in children: chloral hydrate (CH), meperidine (M), and hydroxyzine (H) (regimen A) versus midazolam (MZ), M, and H (regimen B). Patients between 24 and 54 months of age were examined by crossover study design. Behavior was analyzed objectively by the North Carolina Behavior Rating System and subjectively through an operator and monitor success scale. Physiological data were recorded every 5 minutes and at crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 13 publications
0
17
2
1
Order By: Relevance
“…First, the depth of sedation is often greater than recommended for moderate sedation, resulting in concerns and reports of respiratory complications. Furthermore, the elimination half-lives of chloral hydrate, 8-10 h [26] and hydroxyzine, 9-20 h, markedly exceed that of midazolam [27].…”
Section: Oral Sedationmentioning
confidence: 94%
See 1 more Smart Citation
“…First, the depth of sedation is often greater than recommended for moderate sedation, resulting in concerns and reports of respiratory complications. Furthermore, the elimination half-lives of chloral hydrate, 8-10 h [26] and hydroxyzine, 9-20 h, markedly exceed that of midazolam [27].…”
Section: Oral Sedationmentioning
confidence: 94%
“…Two recent studies identified the increased risks of postsedation complications after these long-acting drugs [23,26]. The greater elimination half-lives of chloral hydrate and hydroxyzine increased somnolence in children after the procedure, which is a concern after the children are discharged from the office [23].…”
Section: Oral Sedationmentioning
confidence: 98%
“…Examples might include a dose range of 0.3-0.75, 1.0-1.5, and 1.0 mg/kg of midazolam, meperidine, and hydroxyzine, respectively. One study compared the two "high-dose" triple combinations (i.e., chloral versus midazolam) and found little difference in behaviors [ 29 ]. Yet the rate of quiet behaviors was relatively high suggesting a good sedation outcome.…”
Section: Combinations Of Agentsmentioning
confidence: 99%
“…Trapp [26] (1982) suggested the oral dosage be extended from 50-70 mg/kg because of frequently experienced failure of 50 mg/ kg hypnotic dose to effectively sedate most apprehensive patients. Several studies [37][38][39][40][41][42][43][44][45][46] followed which explored the effectiveness of elevation (and reduction) in its dosage, most of which reported enhanced sedation, but not without increased incidence of emesis, prolonged somnolence, and airway concerns.…”
Section: Most Commonly Used and Studied Agentsmentioning
confidence: 99%
“…Hasty et al [38] prospectively in one of the rare well-designed and controlled studies to date reported similar results. The regimen of CH-hydroxyzinemeperidine has since been among the most studied and utilized until recent times [35,[37][38][39][40][41][42][43][44][45][46].…”
Section: Most Commonly Used and Studied Agentsmentioning
confidence: 99%